Avaliação das técnicas de soldagem Laser, TIG e Plasma de uso odontológico aplicadas às ligas de Co-Cr e Ti-6Al-4V com diferentes configurações de juntas e diferentes diâmetros: análise por meio de teste de tração, teste de flexão, dureza Vicker’s, micro-CT e método de elementos finitos - Castro, Morgana Guilherme de (2016)
Oral rehabilitation of edentulous patients, especially the rehabilitation of edentulous jaws, is a well-documented reality with extensive long-term follow up. This rehabilitation model, which became known as ad modum Branemark Protocol, has been the subject of several studies, both in relation to implants (number, distribution, surface treatment, load times, optimization of the osseointegration process, among others) as in relation to the metallic framework. The studies focused on prosthetic frameworks have been developed in order to optimize the production of these by prefabricated bars and alternative welding techniques to conventional welding. Studies have been conducted to evaluate the types of welding technique; the settings of welding equipment; the types of alloys used; the settings of the joints and mechanical methods of evaluation of these weld joints. Therefore, the following work was proposed which comprises a series of three articles with the overall objective to assess the laser, TIG (Tungsten Inert Gas) and Plasma dental welding techniques applied to Co-Cr and Ti-6Al-4V alloy with different settings joints and different diameters: analysis by means of tensile test, bending test, Vicker's hardness, micro-CT and finite element method. The first article proposed to evaluate the strength of Ti-6Al-4V alloy structures in different diameters with I-shaped joint configuration welded by laser and plasma techniques through tensile test and finite element analysis. The second article proposed to evaluate the strength of Ti-6Al-4V alloy structures in different diameters with I-shaped joint configuration welded by TIG technique, through tensile testing, Vicker's hardness and finite element analysis. The third article proposed to evaluate the correlated mechanical strength with the percentage of total volume of solder and porosities of Co-Cr alloy X-shaped joint configuration welded by TIG technique with different settings of welding equipment, analyses by computed microtomography and bending test. To complete this work, a fourth article was proposed in order to provide a clinical basis for comparison of the values obtained in mechanical tests. Thus, the latter proposed to assess the maximum bite force of two different types of prosthetic rehabilitation and compare their values in subjects with normal occlusion and without any prosthetic rehabilitation.